Industrial Training In The State Of Selangor, As A Complement To The Curriculum Of Naqli And Aqli Knowledge Integration: A Survey Of Organizations Favoured By The Students Of The Faculty Of Quranic And Sunnah Studies, Universiti Sains Islam Malaysia - Mohammed Akhiruddin Ibrahim; Adnan Mohamed Yusoff; Raimizar Rahim; Shaker, MH; Alhamidy, AQU; Sheriff, SS; Zakaria, AR (Int Organization Center Acad Research, 2024)
Indexed by WOS